Informing patients about limits to confidentiality: A qualitative study in prisons. (July 2015) - Elger, Bernice S.; Handtke, Violet; Wangmo, Tenzin
Abstract: Aim: Confidentiality is important in healthcare practice, however, under certain circumstances, confidentiality is breached. In this paper, mental health professionals' (MHPs) practices related to informing imprisoned patients about confidentiality and its limits are presented. Methods: Twenty-four MHPs working in Swiss prisons were interviewed. Data analysis involved qualitative thematic coding and was validated by discussing results with external experts and study participants. Results: For expert evaluations and court-ordered therapies, participants informed patients that information revealed during these consultations is not bound by confidentiality rules. The practice of routinely informing patients about confidentiality and its limits became more complex in voluntary therapies, for which participants described four approaches and provided justifications in favour of or against their use. Conclusions: Further training and continued education are needed to improve physicians' ethical and legal knowledge about confidentiality disclosures. In order to promote ethical practices, it is important to understand and address existing motivations, attitudes and behaviours that impede appropriate patient information. Our study adds important new knowledge about the limits to confidentiality, particularly for providers working with vulnerable populations. Results from this study reflect typical ethical and practical dilemmas faced by and of interest to physicians working in forensic medicine and other related settings.